2018
DOI: 10.2967/jnumed.117.201632
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro and In Vivo Quantifications of Pathologic Tau Deposits and Their Association with Neurodegeneration in Tauopathy Mouse Models

Abstract: Fibrillary tau aggregates in Alzheimer disease and allied neurodegenerative disorders have been visualized in vivo by PET, whereas mechanistic links between PET-detectable tau deposits and neurotoxicity remain elusive. Here, we took advantage of transgenic mouse models of tauopathies to evaluate associations between PET and postmortem measures of tau probe binding and their relation to neuronal loss. PET with a tau probe,C-PBB3 (2-((1E,3E)-4-(6-(C-methylamino)pyridine-3-yl)buta-1,3-dienyl)benzo[d]thiazol-6-ol)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 30 publications
5
73
2
Order By: Relevance
“…Our previous autoradiographic assays demonstrated only minimal nonspecific binding of [ 11 C]PBB3 in the basal ganglia sections . More recently, an in vitro binding assay using human brain homogenates has shown cross‐reactivity of [ 11 C]PBB3 with neither monoamine oxidase‐A nor MAO‐B . Another concern could be binding of [ 11 C]PBB3 to non‐tau protein fibrils, such as α‐synuclein aggregates .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our previous autoradiographic assays demonstrated only minimal nonspecific binding of [ 11 C]PBB3 in the basal ganglia sections . More recently, an in vitro binding assay using human brain homogenates has shown cross‐reactivity of [ 11 C]PBB3 with neither monoamine oxidase‐A nor MAO‐B . Another concern could be binding of [ 11 C]PBB3 to non‐tau protein fibrils, such as α‐synuclein aggregates .…”
Section: Discussionmentioning
confidence: 89%
“…18 More recently, an in vitro binding assay using human brain homogenates has shown cross-reactivity of [ 11 C]PBB3 with neither monoamine oxidase-A nor MAO-B. 38 Another concern could be binding of [ 11 C]PBB3 to non-tau protein fibrils, such as α-synuclein aggregates. 39 As a previous autoradiographic report documented, α-synuclein deposits with very high abundance in MSA brains could be captured by [ 11 C]PBB3, whereas none of the α-synuclein pathologies in dementia with Lewy bodies (DLB) brains were detectable by this radioligand.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo offtarget binding and nonspecific retention of [ 11 C]PBB3 remain undetermined. Our recent in vitro binding assays using human brain homogenates have indicated that [ 11 C]PBB3 does not cross-react with monoamine oxidases A and B, 35 which is in clear distinction from properties of other tau radioligands, including [ 18 F]AV-1451 36 and [ 18 F]THK5351. 37 This observation, however, does not fully ensure the selectivity of [ 11 C]PBB3 for tau fibrils in PET imaging of living patients with tauopathies.…”
Section: Discussionmentioning
confidence: 99%
“…P301S and P301L lines (transgenic for a human 4 repeat tau isoform) [6,[52][53][54], which have become important tools to study the mechanisms of abnormal tau aggregation and deposition in FTD (4 repeat tau) [61] and AD (3 and 4 repeat tau) [25, 33,41]. In the P301L 4 (Thy 1.2, pR5 line) [11,18], P301L (CaMKIIa) [23,43,62] and P301L (tetO) [14] mouse models, tau deposits begin forming before 3 months-of-age in neurons in the entorhinal cortex, hippocampus and later in the cortex, and amygdala; with neuroinflammation and impaired memory functions in hippocampus-and amygdala-dependent tasks manifesting at a later stage [49,50,67]. Brain atrophy and white matter changes indicating neurodegeneration were reported in P301L (CaMKIIa) mouse line around 9 months-of-age [16,23,43,62], which was driven by factors additional to human tau overexpression.…”
Section: Introductionmentioning
confidence: 99%
“…In the P301L 4 (Thy 1.2, pR5 line) [11,18], P301L (CaMKIIa) [23,43,62] and P301L (tetO) [14] mouse models, tau deposits begin forming before 3 months-of-age in neurons in the entorhinal cortex, hippocampus and later in the cortex, and amygdala; with neuroinflammation and impaired memory functions in hippocampus-and amygdala-dependent tasks manifesting at a later stage [49,50,67]. Brain atrophy and white matter changes indicating neurodegeneration were reported in P301L (CaMKIIa) mouse line around 9 months-of-age [16,23,43,62], which was driven by factors additional to human tau overexpression. However, unlike in human patients with tauopathies, brain calcifications have not been reported in transgenic mouse models of human disease.…”
Section: Introductionmentioning
confidence: 99%